Forensic voice comparison in Chile: Balance sheet, projections and challenges (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The objective of this work is to describe the current situation and the projections of forensic voice comparison in Chile, in the light of international standards that focus on the production of reliable evidence that can be used in the courts of justice. To do this, first, the scientific foundations that characterize this branch of forensic sciences are disclosed and, then, on that basis, the situation in Chile and its projections are analyzed and discussed, both in practice and in the forensic research.
Keywords: Forensic voice comparison; international standards; reliable evidence; courts of justice